COMMUNICATING TOURISM IN DOCTOR STRANGER MOVIE - Agustin Diana Wardaningsih; Elisabeth Ngestirosa Endang Woro Kasih (Linguistics and Literature Students' Journal, 2023)
The tourism sector in Indonesia has great potential, both in terms of its natural resources and its people. Tourism has become a unique and enjoyable activity for almost everyone. Films, as a communication medium, are quite effective in promoting tourist destinations and exploring the potential of various regions. This research aims to explore the positive impact on tourist destinations that are affected by the phenomenon in films, leading to their recognition by the general public and an increase in tourist visits to those destinations. The data source for this research is the film Doctor Stranger in 2016 and 2022, including images and film scripts. The results of this research show that films can be used as a medium to promote and boost the popularity of tourist destinations. They can be considered as an alternative promotional tool due to their implicit nature, which tends to resonate more with the target audience. Promoting tourism through films can have positive effects on the featured tourist destinations, including significant improvements in the tourism sector, ranging from increased public awareness of the destinations, increased popularity, to an increase in the number of tourist visitors. Keywords: Dr. Strange film, media, promotion, tourism